Bankruptcy of Large Firms and Exit Mechanisms in Korea - Ilchong Nam; Soogeun Oh (Korea Development Institute (KDI), 2000)
This report deals with two fundamental questions that face the Korean economy: why did so many large firms go bankrupt, and what is wrong with the insolvency mechanisms in Korea? Roughly one third to one half of the medium-sized chaebols went bankrupt or fell into deep financial trouble after the onset of the crisis. In addition, essentially all of the firms belonging to the Daewoo group, one of the top five chaebols, went bankrupt. Some firms affiliated with the other top five chaebols have also fallen into financial difficulties. Massive bankruptcy of chaebol firms led to deep financial difficulties of banks and non-bank financial institutions, which in turn resulted in a massive injection of public funds. Even after the outbreak of the crisis, lack of confidence in the court-supervised bankruptcy proceedings led to the wide use of so-called workouts. The laws on court-supervised bankruptcy proceedings have recently been revised twice, but have not been able to gain full confidence of market participants. The authors claim that the most important factor behind the malfunctioning of bankruptcy proceedings in Korea is the lack of proper corporate governance in financial institutions and large firms. Banks in Korea have been run as if they were government businesses; and as a consequence, they have not been supervised by a proper governance structure that is profit-oriented. Lack of proper governance was the main reason that banks did not act properly as creditors in bankruptcy proceedings and passively followed initiatives of debtor firms and the government. This monograph also contains a chapter focusing on a comparative analysis of bankruptcy proceedings of the following six East Asian countries: Singapore, Malaysia, the Philippines, Thailand, Indonesia, and Korea. The comparative analysis generally confirms that Singapore and Malaysia are equipped with superior institutional infrastructures concerning corporate governance of large firms and reallocation of resources from bankrupt firms, compared to the other four countries that have been adversely affected by the economic crisis. The monograph concludes with a set of proposals that the authors believe is needed to improve the efficiency of bankruptcy proceedings in Korea.
Keywords: 330